(untitled) (Belügyi Szemle, 2025)
Aim: To present the main international trends in civil service staffing, age composition, and mobility, based on recent OECD and EUPAN data, and to highlight the related human resource management challenges and possible strategic responses. Methodology: A comparative analysis drawing on official OECD and EUPAN statistics, reports, and relevant literature. The study examines differences between countries in terms of the proportion of public service employment, workforce age distribution, mobility practices, and structural characteristics. Findings: Public service employment shares remain generally stable across most developed countries, although there are significant variations between OECD members. The aging of the public service workforce is faster than that of the general population, especially in Mediterranean countries, while the proportion of young employees is low, raising concerns about future replacement. Mobility is underutilized as an efficiency-enhancing tool, despite its potential to address skill shortages, distribute competencies more effectively, and support innovation. Value: The study provides a comprehensive, comparative overview of current international trends in the civil service and formulates practical recommendations for human resource policy, particularly in the strategic use of mobility. The results may assist policymakers in long-term workforce planning and fostering generational renewal in public administration.